Endovascular Treatment of Pelvic Congestion Syndrome: Visual Analog Scale Follow-Up - Senechal, Quentin; Echegut, Perrine; Bravetti, Marine; Florin, Marie; Jarboui, Lamia; Bouaboua, Mehdi; Teriitehau, Christophe; Feignoux, Jacques; Legou, Francois; Pessis, Eric (Frontiers in Cardiovascular Medicine, 2021)
PURPOSE: To evaluate medium-term clinical outcome of transcatheter embolization and stenting in women with chronic pelvic pain caused by chronic pelvic congestion syndrome or lower limb varices. MATERIALS AND METHODS: The study population included 327 consecutively recruited patients referred to the interventional radiology unit from January 2014 to December 2019, due to chronic pelvic congestion (312; 95%) or lower limb varices (236; 72%). Preprocedural pelvic, transvaginal Doppler ultrasonography (US) and MRI was conducted in all patients and revealed anatomical varicosities and incompetent pelvic veins in 312. In all patients, selective catheterization demonstrated uterine venous engorgement, ovarian plexus congestion, or pelvic vein filling. Patients were followed-up at 1 month, 6, 12, and yearly thereafter. They were contacted by telephone in 2020 to assess pain perception and quality of life using visual analog scales from 0 to 10, with assessments made at baseline and last follow-up. Of the 327 patients (mean age, 42±12 years), 312 were suffering from pelvic congestion syndrome, and 236 from lower limb varices. All underwent embolization using ethylene vinyl alcohol copolymer (Onyx®). A cohort of patients who also underwent Nutcracker Syndrome angioplasty (6.7%) and May Thurner syndrome angioplasty (14%) with stent placement. RESULTS: Overall, 307 patients attended 12-month follow-up visits, and 288 (82%) completed the telephone survey at mean 39(±18)-month post-intervention. Main pelvic pain significantly improved from 6.9 (±2.4) pre- to 2.0 (±2.4) post-embolization (P <.001), as did specific symptoms in each category, and quality of life. Improvement or disappearance of pain was achieved in 266/288 (92.36%) patients, with improved quality of life in 276/288 (95.8%). There were 20 undesirable events reported on follow-up. CONCLUSION: Pelvic veins embolization (Onyx®) is an effective and safe procedure, with high clinical success and quality of life improvement rates